GENDER IN FIQH PERSPECTIVE - Mahmudah, Nurul; muammar, muammar; Muthoharoh, Lailatul (Jurnal Studi Gender dan Anak, 2019)
In contrast to the concept of sex (sex) or nature, Gender only contains the functions and social roles of men and women, which are formed from the environment in which a person resides / lives. Thus, the concept of gender is a trait inherent in men and women who are constructed socially and culturally. Like, women in the heart are gentle, emotional and motherly, while men are known to be strong, rational and mighty. Gender differences have led to injustice, both for men and for women. The manifestation of gender inequality can be seen in the form of marginalization, subordination, stereotyping, violence and workload